2019
DOI: 10.1161/str.0000000000000183
|View full text |Cite
|
Sign up to set email alerts
|

Management of Stroke in Neonates and Children: A Scientific Statement From the American Heart Association/American Stroke Association

Abstract: Purpose-Much has transpired since the last scientific statement on pediatric stroke was published 10 years ago. Although stroke has long been recognized as an adult health problem causing substantial morbidity and mortality, it is also an important cause of acquired brain injury in young patients, occurring most commonly in the neonate and throughout childhood. This scientific statement represents a synthesis of data and a consensus of the leading experts in childhood cardiovascular disease and stroke. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
587
6
26

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 526 publications
(622 citation statements)
references
References 511 publications
(687 reference statements)
3
587
6
26
Order By: Relevance
“…The American Heart Association (AHA) Guidelines on Management of Stroke in Infants and Children suggests reasonable evaluation for the more common prothrombotic states even when another stroke risk factor has been identified (Class IIa, Level of Evidence C). 29 The updated 2019 AHA guidelines for Management of Stroke in Neonates and Children 30 and the AHA Guidelines on Prevention and Treatment of Thrombosis in Pediatric and Congenital Heart Disease concur with these recommendations and suggest considering evaluation for inherited or acquired prothrombotic risk factors in children with heart disease who have a stroke (Class IIa, Level of Evidence B). 6 Although routine testing for hypercoaguability after neonatal stroke may not be indicated in the absence of cardiac disease, 31 in neonates and children with CHD, a thrombophilia evaluation may be appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…The American Heart Association (AHA) Guidelines on Management of Stroke in Infants and Children suggests reasonable evaluation for the more common prothrombotic states even when another stroke risk factor has been identified (Class IIa, Level of Evidence C). 29 The updated 2019 AHA guidelines for Management of Stroke in Neonates and Children 30 and the AHA Guidelines on Prevention and Treatment of Thrombosis in Pediatric and Congenital Heart Disease concur with these recommendations and suggest considering evaluation for inherited or acquired prothrombotic risk factors in children with heart disease who have a stroke (Class IIa, Level of Evidence B). 6 Although routine testing for hypercoaguability after neonatal stroke may not be indicated in the absence of cardiac disease, 31 in neonates and children with CHD, a thrombophilia evaluation may be appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] This requires enhanced community education and an organized system of evaluation and management once a patient presents for medical care. 20 We have shown that the establishment of a stroke alert system at a tertiary children's hospital, coupled with extensive internal educational efforts, significantly decreases the median time to diagnosis by neuroimaging of patients presenting to the ED with brain attack symptoms. This finding represents an important first step in ensuring that a greater proportion of children with AIS are diagnosed within a time frame that enables treatment with acute interventions.…”
Section: Discussionmentioning
confidence: 98%
“…Aspirin therapy is given for thromboprophylaxis prior to surgery and to promote patency of the graft vessels. 25 There has been a historical reluctance to use aspirin in SCD patients with moyamoya due to a concern that its use may precipitate intracranial hemorrhage. However, this increased risk generally occurs well into adulthood and is not exclusive to SCD-associated moyamoya, so clinical practice trends are starting to change.…”
Section: Discussionmentioning
confidence: 99%
“…25 There has been a historical reluctance to use aspirin in SCD patients with moyamoya due to a concern that its use may precipitate intracranial hemorrhage. Aspirin therapy is given for thromboprophylaxis prior to surgery and to promote patency of the graft vessels.…”
Section: And the Stroke Prevention Trial In Sickle Cell Anemia (Stop)mentioning
confidence: 99%